Annual Plan 2004-2005 (Volume-II) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2004)
The effort now is to make the learning more enjoyable and taking such effective steps to make the study of the children in schools to be more pleasant. In order to achieve this objective adequate play way material is to be provided in the schools. Children are encouraged to use their own hand and skill to learn the things and have a feel of it. The material interalia could include good quality audio-visual equipment, electrical equipments, mechanical toys and other related teaching and learning materials to understand various concepts of learning.
Planning Department, Government of National Capital Territory of Delhi